Imperial Mecca - Low, Michael Christopher.
1 online resource (415 pages)
Keywords: Michael Christopher Low analyzes the late Ottoman hajj and Hijaz region as transimperial spaces, reshaped by the competing forces of Istanbul's project of frontier modernization and the extraterritorial reach of British India's steamship empire in the Indian Ocean and Red Sea.